Nickel-based catalyst taking halloysite as carrier, preparation method of nickel-based catalyst and application of nickel-based catalyst in preparation of methane by hydrogenation of carbon dioxide
By using natural eloite as a support, combined with impregnation method and ultrasonic dispersion and other technologies, a nickel-based catalyst was prepared, which solved the problems of low activity and poor stability of existing catalysts in carbon dioxide methanation reaction, and achieved efficient and low-cost catalytic performance.
Patent Information
- Application Number
- CN202311390840.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the carbon dioxide methanation reaction, the existing Ni-based catalysts have problems such as low dispersion of active components, easy sintering at high temperatures and poor stability, and the preparation conditions of traditional molecular sieves are harsh and costly.
Using natural elosite as a support, nickel-based catalyst was prepared by combining nickel salt with elosite through impregnation. The method is simple and has low cost, and the activity and stability of the catalyst are improved through steps such as ultrasonic dispersion, vacuum drying and calcination.
The prepared nickel-based catalyst exhibits excellent activity and methane selectivity in carbon dioxide methanation reaction, with a CO2 conversion rate of up to 100.0%, a CH4 selectivity of up to 99%, and has long-term stability and low production costs.
Smart Images

Figure CN119869526A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon dioxide methanation catalysts, and in particular to a nickel-based catalyst using halloysite as a carrier, a preparation method and application thereof in the hydrogenation of carbon dioxide to methane. Background Art
[0002] In recent decades, people have used a large amount of disposable energy such as coal and oil, and a large amount of carbon dioxide will be emitted during the use of the project, which will cause irreversible damage to the environment, such as the greenhouse effect and sea level rise. Using H2 to convert CO2 into high-value-added products and fuels is considered to be one of the most effective ways to reduce CO2 emissions. Compared with other reactions that form alcohols and hydrocarbons, CO2 methanation reaction is thermodynamically (CO2+4H2→CH4+2H2O, ΔG 298K =-114kJ / mol) has great advantages and has been widely studied. At the same time, the product CH4 is considered to be a clean fuel and has important uses in liquefied natural gas (LNG), fuel cells and power-to-gas technology.
[0003] At present, most methanation catalysts are supported catalysts, including precious metal and non-precious metal catalysts. Among them, Ni-based catalysts have been industrialized due to their relatively high activity, selectivity and low cost, but there are still problems such as low dispersion of active components, easy sintering at high temperature and poor stability. Selecting carriers with different structures is one of the effective ways to solve the above problems. Studies have shown that the carrier usually affects the catalytic performance of the catalyst by affecting the metal-carrier interaction and the dispersion of the active components. In recent years, various synthetic mesoporous molecular sieve materials, such as MSN, MCM-41, SBA-15 (16), etc., have been widely used to prepare highly dispersed Ni-based catalysts due to their large specific surface area, pore volume and highly ordered pore structure. These catalysts show excellent activity and stability in CO2 methanation reactions. However, the preparation conditions of molecular sieves are harsh, and the preparation process is often environmentally unfriendly. The large-scale preparation conditions require high requirements, which greatly increases the production cost. Halloysite (HNTs, Al2Si2O5(OH)4·nH2O) is a natural aluminosilicate mineral material, with its inner and outer surfaces composed of aluminum oxide octahedrons and silicon oxide tetrahedrons respectively. The difference in charge properties of the inner and outer surfaces can selectively load metal ions for different chemical reactions. At the same time, halloysite has the same high porosity as mesoporous molecular sieves and other materials, and is abundant in reserves, low in cost, mechanically stable, and environmentally friendly. Using it as a carrier for methanation catalysts is of great industrial value. Summary of the invention
[0004] The purpose of the present invention is to provide a nickel-based catalyst with halloysite as a carrier, a preparation method and its application in the hydrogenation of carbon dioxide to methane. The catalyst preparation method of the present invention is simple, the production cost is low, and it shows high activity and long-term stability in the CO2 methanation reaction.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] The invention provides a nickel-based catalyst using halloysite as a carrier, using natural mineral material halloysite as a carrier and metal Ni as an active component; wherein the content of the metal Ni is 5wt% to 40wt% and the balance is halloysite.
[0007] Furthermore, the tube length of the halloysite is 50 to 500 nm, preferably 100 to 300 nm, the inner diameter of the tube is 8 to 40 nm, preferably 27 nm, the outer diameter of the tube is 30 to 150 nm, preferably 65 nm, and the specific surface area is 60 to 240 m 2 / g, preferably 233m 2 / g, pore volume is 0.2~0.8cm 3 / g, preferably 0.7cm 3 / g, and the pore diameter is 2 to 40 nm, preferably 12 nm.
[0008] The specific surface area of the prepared nickel-based catalyst with halloysite as the carrier is 60 to 150 m 2 / g, preferably 84m 2 / g, pore volume is 0.2~0.5cm 3 / g, preferably 0.23cm 3 / g, and the pore diameter is 2 to 40 nm, preferably 11 nm.
[0009] The active component Ni exists in the form of NiO and Ni2O3.
[0010] The present invention also provides a method for preparing a nickel-based catalyst using halloysite as a carrier, comprising the following steps:
[0011] The nickel salt is dissolved in a solvent, and a certain amount of additives are added to prepare a precursor solution of a metal active component, and then a dry halloysite carrier is added, and the halloysite is impregnated in the precursor solution by an impregnation method, and the nickel-based catalyst with the halloysite as a carrier is obtained after ultrasonic dispersion, standing, vacuum drying, calcination, and grinding;
[0012] The nickel salt is at least one of chloride, acetate, oxalate, nitrate, sulfate or phosphate of the active component Ni;
[0013] The solvent is at least one of deionized water, methanol, ethanol, n-butanol, n-hexanol, acetic acid, ethyl acetate, n-pentane, n-hexane, and n-heptane.
[0014] The additive is at least one of citric acid, glucose, ethylene glycol, polysorbate, and glycerol; the mass ratio of the additive to the nickel salt is (0-1.2):1, and the additive will be removed during the calcination process and does not exist in the components of the final catalyst;
[0015] The mass ratio of the nickel salt to the halloysite is (0.1-0.6):1.
[0016] Furthermore, the impregnation method is an equal volume impregnation method or an excess impregnation method, the impregnation temperature is room temperature, and the impregnation time is 4 to 24 hours, preferably 6 to 12 hours;
[0017] The ultrasonic dispersion time is 0.5 to 2 hours, preferably 0.5 to 1 hour;
[0018] The vacuum drying temperature is 40 to 100° C., preferably 60 to 80° C., and the drying time is 6 to 48 hours, preferably 12 to 24 hours;
[0019] The calcination atmosphere is air, the calcination heating rate is 1-5°C / min, the calcination temperature is 400-700°C, preferably 450-550°C, and the calcination time is 2-6h, preferably 3-5h.
[0020] The present invention also provides an application of the nickel-based catalyst with halloysite as a carrier in a CO2 methanation reaction, characterized in that the process conditions of the CO2 methanation reaction are: the reaction gas volume space velocity is 3500-35000 mL / g / h, the pressure is from normal pressure to 5.0 MPa, the temperature is 250-550°C, and the H2 / CO2 ratio in the reaction gas is 2-4.
[0021] The present invention discloses the following technical effects:
[0022] (1) The nickel-based catalyst with halloysite as a carrier according to the present invention exhibits excellent activity and methane selectivity in the CO2 methanation reaction. The nickel-based catalyst is active in the temperature range of 250-550°C, and the optimal reaction temperature range is 300-400°C. When the catalyst reaches the optimal catalytic activity, the CO2 conversion rate is 100.0% and the CH4 selectivity can reach at least 99%.
[0023] (2) The nickel-based catalyst with halloysite as a carrier of the present invention uses halloysite with large specific surface area, good heat transfer properties and stable chemical properties as a carrier. The interaction between the metal and the carrier in the prepared catalyst is strong, and the active components are highly dispersed on the surface of the carrier. Therefore, the catalyst has the advantages of high catalytic activity, good selectivity, and long life. The catalyst does not contain precious metal components, the preparation method is simple, the cost is low, and it has potential industrial application value.
[0024] (3) The nickel-based catalyst with halloysite as the carrier described in the present invention is a natural mineral material, which is non-toxic and has large reserves. Compared with the strict preparation conditions of traditional molecular sieves (MCM-41, SBA-15 (16)) and the large amount of pollutants discharged during the preparation process, the catalyst with halloysite as the carrier has a high degree of scalability. In addition, the presence of the tubular structure of halloysite is conducive to mass transfer and heat transfer during the catalytic reaction, which can effectively avoid high-temperature sintering of metal active components. It has shown broad application prospects in the fields of adsorption, biomedicine, environment and catalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the TEM image of natural halloysite;
[0026] Figure 2 XRD patterns of the catalysts prepared in Examples 1 and 6 of the present invention;
[0027] Figure 3 This is a TEM image of the catalyst prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0028] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0029] The "room temperature" of the present invention refers to 15 to 30°C, preferably 20 to 25°C.
[0030] The "normal pressure" in the present invention refers to 0.1 MPa.
[0031] If not otherwise specified, deionized water is generally used as the impregnation solvent in the present invention.
[0032] The detailed information of the reagents used in the examples of the present invention is shown in Table 1:
[0033] Table 1
[0034]
[0035] Example 1
[0036] 1.7837g of nickel nitrate hexahydrate was dissolved in 1.5g of deionized water to prepare an aqueous solution of nickel nitrate. Then, an equal volume of 1.8g of the above-mentioned halloysite carrier was immersed in the aqueous solution of nickel nitrate, ultrasonically dispersed at room temperature for 1h, and allowed to stand for 6h. Subsequently, the impregnated sample was dried in a vacuum oven at 80°C for 12h. The dried solid product was placed in a muffle furnace, calcined at 550°C in an air atmosphere for 5h, and naturally cooled to room temperature to obtain a nickel-based catalyst with a mass fraction of 17wt%.
[0037] Example 2
[0038] 1.7837g of nickel nitrate hexahydrate was dissolved in 1.5g of deionized water, and 0.25g of citric acid monohydrate was added to prepare an aqueous solution of nickel nitrate. Then, an equal volume of 1.8g of the above-mentioned halloysite carrier was immersed in the aqueous solution of nickel nitrate, ultrasonically dispersed at room temperature for 1h, and allowed to stand for 6h. Subsequently, the impregnated sample was dried in a vacuum oven at 80°C for 12h. The dried solid product was placed in a muffle furnace, calcined at 550°C in an air atmosphere for 5h, and naturally cooled to room temperature to obtain a nickel-based catalyst with a mass fraction of 17wt%.
[0039] Example 3
[0040] Glucose was used to replace the citric acid monohydrate in Example 2, and the remaining steps were the same as in Example 2 to prepare a nickel-based catalyst with a mass fraction of 17 wt%.
[0041] Example 4
[0042] 1.7837g of nickel nitrate hexahydrate was dissolved in 1.5g of deionized water to prepare an aqueous solution of nickel nitrate. Then, an equal volume of 1.8g of the above-mentioned halloysite carrier was immersed in the ethanol solution of nickel nitrate, ultrasonically dispersed at room temperature for 1h, and allowed to stand for 6h. Subsequently, the impregnated sample was dried in a vacuum oven at 80°C for 12h. The dried solid product was placed in a muffle furnace, calcined at 550°C in an air atmosphere for 5h, and naturally cooled to room temperature to obtain a nickel-based catalyst with a mass fraction of 17wt%.
[0043] Example 5
[0044] Weigh 1.8g of halloysite and add it to 40mL of n-hexane solution, ultrasonically disperse it for 15min, then dissolve 1.7837g of nickel nitrate hexahydrate in 1.5g of deionized water, and then add the solution dropwise to the cyclohexane solution in which halloysite is dispersed, ultrasonicate it for 1h and let it stand for 12h. Subsequently, filter the solution and place the sample in a vacuum oven at 80℃ to dry for 12h, then calcine it in air at 550℃ for 5h, and naturally cool it to room temperature to obtain a nickel-based catalyst with a mass fraction of 17wt%.
[0045] Example 6
[0046] 4.4592 g of nickel nitrate hexahydrate was used to replace 1.7837 g of nickel nitrate hexahydrate in Example 1. The remaining steps were the same as in Example 1 to prepare a nickel-based catalyst with a mass fraction of 30 wt%.
[0047] Comparative Example 1
[0048] 1.7837g of nickel nitrate hexahydrate was dissolved in 1.5g of deionized water to prepare an aqueous solution of nickel nitrate. Then, an equal volume of 1.8g of SBA-15 carrier was immersed in the aqueous solution of nickel nitrate, ultrasonically dispersed at room temperature for 1h, and allowed to stand for 6h. Subsequently, the impregnated sample was dried in a vacuum oven at 80°C for 12h. The dried solid product was placed in a muffle furnace, calcined at 550°C in an air atmosphere for 5h, and naturally cooled to room temperature. After grinding, a nickel-based catalyst with a mass fraction of 17wt% was obtained.
[0049] Comparative Example 2
[0050] The SBA-15 in Comparative Example 2 was replaced by a mesoporous silica carrier, and the remaining steps were the same as those in Example 2 to prepare a nickel-based catalyst with a mass fraction of 17 wt%.
[0051] The catalysts prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were used in the CO2 methanation reaction.
[0052] Weigh 0.48g of the catalyst prepared in Examples 1 to 6 and Comparative Examples 1 to 2, and load it into a fixed bed reactor with a diameter of 6nm using the sandwich method. Before the reaction, purge the air with N2, and then reduce the catalyst at 500°C and in a pure H2 atmosphere for 2h. After the reduction is completed, the N2 atmosphere is lowered to the reaction temperature, and the reaction gas is switched to test the performance of the catalyst. The reaction gas composition is H2:CO2:N2=4:1:1, the reaction pressure is normal pressure, the reaction temperature is 250~550°C, and the reaction gas volume space velocity is 15,000mL / g / h. The reaction gas product is analyzed online using a gas chromatograph and a thermal conductivity detector (TCD).
[0053] The CO2 conversion rate and CH4 selectivity were calculated as follows, and the optimal catalytic activity results of the catalysts are listed in Table 2:
[0054] CO2 conversion rate: Conv%(CO2)=(1-CO2 amount in the product / CO2 amount in the raw gas)×100%;
[0055] CH4 selectivity: Sele%(CH4)=(amount of CO2 converted to CH4 / amount of CO2 converted)×100%;
[0056] Table 2
[0057]
[0058] Comparing the catalyst activity data of Examples 1 to 6 and Comparative Examples 1 to 2, it can be seen that the nickel-based catalyst with halloysite as the carrier exhibits better catalytic performance in the CO2 methanation reaction. Combined with the data of Examples 1 to 5, it can also be found that the introduction of additives and organic solvents during the impregnation process can improve the catalytic performance of the catalysis to a certain extent. This is because the introduction of small molecule additives and organic solvents can reduce the size of the active component particles, the dispersion of the metal active components is improved, and the smaller Ni particle surface has more active sites, which is conducive to the adsorption and activation of the reaction gas. In addition, combined with the data of Example 1 and Example 6, the increase in the amount of metal Ni loading can further improve the catalytic activity of the catalyst, and because the unique tubular structure and pore structure of halloysite have a confining effect, the agglomeration of metal particles can be effectively suppressed during the catalyst preparation and reaction process, thereby improving the activity and stability of the catalyst. It was found from the experimental process that the preparation process of traditional molecular sieves is complicated, the conditions are harsh, and the molecular sieve carrier and the catalyst precursor are involved in the catalyst preparation process. Two high-temperature roastings, a long preparation cycle, and large-scale production cannot be achieved. The present invention uses natural halloysite as a carrier, which is abundant in reserves, low in price, simple in catalyst preparation method, and does not contain precious metal components. Under optimal conditions, the nickel-based catalyst prepared in the present invention can achieve a carbon dioxide conversion rate of 100.0% and a methane selectivity of at least 99%, which has great industrial prospects.
[0059] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A nickel-based catalyst with halloysite as a carrier, characterized in that: The catalyst uses halloysite as a carrier and metal Ni as an active component; wherein the content of metal Ni is 5wt% to 40wt% of the catalyst, and the remainder is halloysite.
2. A nickel-based catalyst with halloysite as a carrier according to claim 1, characterized in that: The tube length of the halloysite is 50-500 nm, the inner diameter of the tube is 8-40 nm, the outer diameter of the tube is 30-150 nm, and the specific surface area is 60-240 m 2 / g, pore volume is 0.2~0.8cm 3 / g, pore size is 2~40nm.
3. A method for preparing a nickel-based catalyst as claimed in claim 1, characterized in that: The steps include: The nickel salt is dissolved in a solvent, and a certain amount of additives are added to prepare a precursor solution of a metal active component, and then a dry halloysite carrier is added, and the halloysite is impregnated in the precursor solution by an impregnation method, and the nickel-based catalyst with the halloysite as a carrier is obtained after ultrasonic dispersion, standing, vacuum drying, roasting, and grinding; Wherein, the mass ratio of the additive to the nickel salt is (0-1.2):1, and the mass ratio of the nickel salt to the halloysite is (0.1-0.6):1; The nickel salt is at least one of chloride, acetate, oxalate, nitrate, sulfate or phosphate of the active component Ni; The additive is at least one of citric acid, glucose, ethylene glycol, polysorbate, and glycerol; The solvent is at least one of deionized water, methanol, ethanol, n-butanol, n-hexanol, acetic acid, ethyl acetate, n-pentane, n-hexane, and n-heptane.
4. The method for preparing a nickel-based catalyst according to claim 3, characterized in that: The impregnation method is an equal volume impregnation method or an excess impregnation method, the impregnation temperature is room temperature, and the duration is 4 to 24 hours; The ultrasonic dispersion time is 0.5 to 2 hours; The vacuum drying temperature is 40-100°C and the drying time is 6-48h; The calcination temperature is 400-700° C., the heating rate is 1-5° C. / min, and the calcination time is 2-6 hours.
5. Use of the nickel-based catalyst as claimed in claim 1 or 2 in CO2 hydrogenation to methane, characterized in that: The process conditions of the CO2 methanation reaction are: the reaction gas volume space velocity is 3500-35000 mL / g / h, the pressure is from atmospheric pressure to 5.0 MPa, the temperature is 250-550°C, and the H2 / CO2 ratio in the reaction gas is 2-4.
Citation Information
Patent Citations
Preparation method and application of halloysite-loaded cobalt-base catalyst
CN102319567A
Nickel-based methanation catalyst dispersive in SBA-15 ducts and preparation and application thereof
CN107199047A
Nickel-based catalyst prepared from organic molecule additive and application of nickel-based catalyst in methanation reaction
CN107519911A
Nickel-based catalyst, preparation method and application thereof
CN113522295A
Halloysite-loaded nickel-based nano-catalyst as well as preparation method and application thereof
CN115532265A